HEALTH LOCUS OF CONTROL DAN SELF-EFFICACY PASIEN DM TIPE 2 DENGAN PENERAPAN MODIFIKASI PSIKOEDUKASI - Yulis Hati; Fitriani Fadillah; Muslimah Pase (Jurnal Keperawatan Priority, 2021)
It is feared that the high prevalence of DM will increase the risk of comorbidities as a result of complications of this disease. Complications that occur in DM in Indonesia include neuropathy complications in 60%, coronary heart disease at 20.5%, diabetic ulcers at 15%, retinopathy at 10%, and nephropathy at 7.1%. The study aims to treat diabetes mellitus patients with a lifelong disease that must be well managed and compliant to avoid complications that worsen the patient's condition. The type of research used in this study is quasi-experimental research. This research design using a pretest-posttest control group design. The population was in this study were elderly people suffering from Type 2 Diabetes Mellitus. From the data of the Puskesmas, the sample was taken using a systematic random sampling method. It was found that 35 respondents were in the working area of ​​Puskesmas Sentosa Baru. Psychoeducation was given for 3 weeks and every week a random blood glucose level was checked. The results of this study are the influence of the application of psychoeducation on self-efficacy in Type 2 DM patients in the work area of ​​the Puskesmas Sentosa Baru (p=0,000). This study concludes that there is an effect of the application of psychoeducation on self-efficacy in type 2 DM patients in the work area of ​​the Puskesmas Sentosa Baru.